Barriers and Strategies of Fruit and Vegetable Consumption in High School Students in Sanandaj - Ghobad Moradi; Ardeshir Rahimzadeh; Sorayya Amani; Jahanbakhsh Yousefi; Khaled Rahmani; Sharareh Bagheri (Journal of Education and Community Health)
Background and Objective: Adolescence is one of the most important periods of life, in which the lifestyle is formed and established. On the other hand, the use of appropriate amounts of fruits and vegetables in daily diet is one of the important strategies for preventing illness and promoting health, especially during adolescence. This study was conducted with the aim of investigating barriers and strategies of fruit and vegetable consumption in high school students. Participants and Methods: This qualitative study was conducted, using a semi-structured questionnaire in a focused group discussion among high school students (male and female) in Snandaj in 2017. The participants included 20 females and 16 males, who participated in 4 group discussions in the high schools. All group discussions were recorded, analyzed, and categorized immediately after completion. Due to the similarity of the propositions extracted from the group discussions with the Pen-3 pattern, this model was used for analysis. Results: The concepts extracted based on the model were categorized in six sections including positive and negative perceptions, positive and negative enablers, and positive and negative amplifiers. Some of the findings of the present study were low nutritional knowledge, beliefs and values, the impact of peers, the role of parents, the media, and access. Conclusion: Adolescent barriers to the consumption of fruits and vegetables are not merely dependent on the person themselves and are influenced by external factors. Therefore, in designing interventions to improve the consumption of fruits and vegetables, all effective factors should be addressed.